Serum NLRP3 and S1P as Potential Diagnostic and Prognostic Biomarkers in Female Metastatic and Non-Metastatic Breast Cancer Patients - Anas R. Soltan; Amany M. Kamal; Reham A. A. El-Shimy; Hala O. El-Mesallamy (Archives of Pharmaceutical Sciences Ain Shams University)
Background: Breast cancer (BC) is considered the main cause of death in women worldwide. Overexpression of Sphingosine 1-phosphate (S1P) receptors in estrogen receptor (ER) negative BC patients is linked to poor prognosis. In vitro, the bioactive lipid metabolite S1P induced Nod-like receptor3 (NLRP3) dependent activation of caspase-1 and secretion of interleukin-1beta (IL-1). Objective: Evaluate serum levels of S1P and NLRP3 to examine their potential as diagnostic and prognostic biomarkers for BC. Methods: The study involved 26 metastatic BC patients, 30 non-metastatic BC patients, and 20 healthy control volunteers. NLRP3, S1P, and cancer antigen15.3 (CA 15.3) serum levels were analyzed using ELISA. Statistical analysis involved Mann–Whitney U, Kruskall-Wallis tests, and Receiver operating curve (ROC) analysis. Results: Serum levels of NLRP3 were significantly lower in non-metastatic than in metastatic BC (P < 0.001) and serum levels of S1P were significantly lower in metastatic than in non-metastatic BC and control (P < 0.001). Single ROC analysis showed that NLRP3 has a very good diagnostic value in early and late-stage BC (P< 0.0001), but a poor prognostic value in predicting metastasis (P=0.1392). In contrast, S1P has an excellent diagnostic value in late-stage BC (P <0.0001), and an excellent prognostic value in predicting metastasis (P<0.0001), but a poor diagnostic value in early-stage BC (P =0.1781). The diagnostic and prognostic value of the studied biomarkers improved by combining every two markers together (P<0.001). Conclusion: NLRP3 and S1P could be promising novel diagnostic and prognostic biomarkers of BC either used alone or in combination with CA 15.3.